2002
DOI: 10.1111/j.1749-6632.2002.tb05950.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Coxsackievirus B3 Pathogenesis

Abstract: The development of high throughput genomic and bioinformatic analysis tools, coupled with established molecular techniques, has allowed new insights into the pathogenesis of infectious diseases. In humans, coxasackievirus B3 (CVB3) is the primary etiological agent of viral myocarditis, an inflammatory disease process involving the heart muscle. Early host cellular survival and apoptotic mechanisms during viral infections, as well as immune events, affect myocarditis progression and outcome. Therefore, our labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 52 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…Secondly, mice infected by CVB3 were possibly died of multiple organ dysfunctions. 2 Here, as we focused on viral myocarditis we did not investigate the role of CXCL10 in other organ diseases following virus infection. It is unknown whether CXCL10 affects the viral replication and inflammation in other susceptible organs, such as liver and pancreas.…”
Section: Yuan Et Al Cxcl10 In Viral Myocarditis 635mentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, mice infected by CVB3 were possibly died of multiple organ dysfunctions. 2 Here, as we focused on viral myocarditis we did not investigate the role of CXCL10 in other organ diseases following virus infection. It is unknown whether CXCL10 affects the viral replication and inflammation in other susceptible organs, such as liver and pancreas.…”
Section: Yuan Et Al Cxcl10 In Viral Myocarditis 635mentioning
confidence: 99%
“…1 This disease is composed of three distinct stages including viremic injury, immune infiltration, and reclamation. 2 Earlier studies have suggested that mechanisms of viral myocarditis include direct myocyte injury by CVB3 and subsequent immune-mediated damage of the heart. 3,4 The essential role of the immune response in combating viral myocarditis has been demonstrated by recent studies using a series of knockout (KO) mice.…”
mentioning
confidence: 99%
“…Picornaviridae, is one of the most common causative pathogens for human viral myocarditis and its sequela, dilated cardiomyopathy (DCM) (3,41,42). CVB3-induced viral myocarditis is initially considered an immune-mediated disease (40), but results from our laboratory and others have shown that CVB3 can also directly injure cardiomyocytes in infected hearts (12).…”
mentioning
confidence: 99%
“…After the early observations noted above, almost simultaneously, multiple reports from different laboratories showed the role of another part of the network, ERK1/2, whose phosphorylation is required for CVB3 infection [95][96][97]. ERK1/2 is a member of the mitogen-activated protein kinases (MAPKs), which are evolutionarily conserved enzymes relaying extracellular signals from cell surface receptors to critical targets within cells, and thus regulate biological events such as cell proliferation, differentiation and stress responses [98].…”
Section: • • Signal-transduction Pathways and Cvb3 Infectionmentioning
confidence: 97%
“…ERK1/2 is a member of the mitogen-activated protein kinases (MAPKs), which are evolutionarily conserved enzymes relaying extracellular signals from cell surface receptors to critical targets within cells, and thus regulate biological events such as cell proliferation, differentiation and stress responses [98]. A number of studies have revealed that the early activation of ERK1/2 may stem from the engagement of CVB3 with its main receptor CAR, co-receptor DAF or both [96][97]99]. There is also a mechanism that partly depicts how ERK1/2 phosphorylation is associated with replication of CVB3 at later times postinfection.…”
Section: • • Signal-transduction Pathways and Cvb3 Infectionmentioning
confidence: 99%